A construção da produção textual dos educandos no ensino fundamental - Garcia, Joelma dos Santos Barbosa Linhares (2017)
The objective of the present study was to analyze, in the light of the literature and a classroom experience of textual production, the didactic-pedagogical and methodological actions of the Portuguese Language Teachers, focusing on the practice of reading and writing, from Of a workshop proposed for this purpose. The methodology was based on bibliographic review, observation and researchaction, through an evaluation of the evaluation of the results of the application of the workshop in a classroom of students of the ninth grade of elementary school, a municipal school In Juazeiro do Norte-CE. The specific objectives were: to analyze the pedagogical practices applied in relation to the textual practice in the school in question; Identify which pedagogical practices stimulate reading and writing in the classroom; To point out positive and negative aspects in the application of the pedagogical workshop as an instrument of the students' empowerment in relation to the stimulus of writing. Encouraged by the workshop, the students developed their creativity through their texts, reflections of their experiences and knowledge, resulting in the final product, moral stories, whose textual genre - the fable - is characterized according to Barbosa (2001) as a genre Narrative that records the experiences and way of life of individuals, where, through orality and writing, lessons are learned that are important for social life. We conclude that the conception that the literary text is plural and interrelated with thematic codes, linguistic, stylistic, among others. We understand that the practices in textual production still seem marked, by traditional methods of teaching, confirming an education that determines to the student how he should receive the information and the concepts and how he should proceed. Contrary to such perspectives, workshops for textual production have acted as an important tool to motivate students and provide them with the freedom to create within a certain context. In this sense, our work collaborated to show the importance of breaking away from the teaching strategies that put the teacher as the only center of knowledge.